2015
DOI: 10.1186/s13028-014-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of canid herpesvirus-1 infection in stillborn and dead neonatal puppies in Denmark

Abstract: BackgroundCanid herpesvirus-1 (CaHV-1) infection in puppies less than three weeks of age is often reported to be associated with a lethal generalized necrotizing inflammation and since the discovery of the virus in 1965 several reports of neonatal infections have been published. However, the significance of CaHV-1 for peri- and neonatal mortality in puppies remains unclear. Therefore, we examined stillborn and dead neonatal puppies in Denmark to determine the prevalence of infection and further to correlate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 13 publications
(17 reference statements)
2
46
0
7
Order By: Relevance
“…However, most CaHV-1-infected PCR-positive dogs presented with disseminated necrotic and hemorrhagic lesions in the absence of herpesviral inclusion bodies [22], which was in agreement with this study. Moreover, a cross-sectional study of 57 dead puppies in Denmark revealed that 22.8% of the dead puppies were positive for CaHV-1 infections when assayed by real-time PCR (qPCR), but analysis of the histological lesions was not consistent and the in situ hybridization results were mostly negative, except for one sample that contained a few positive cells [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most CaHV-1-infected PCR-positive dogs presented with disseminated necrotic and hemorrhagic lesions in the absence of herpesviral inclusion bodies [22], which was in agreement with this study. Moreover, a cross-sectional study of 57 dead puppies in Denmark revealed that 22.8% of the dead puppies were positive for CaHV-1 infections when assayed by real-time PCR (qPCR), but analysis of the histological lesions was not consistent and the in situ hybridization results were mostly negative, except for one sample that contained a few positive cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic intranuclear inclusion bodies might be present in the epithelial cells of the trachea, bronchi, lung, liver and kidneys, suggesting that inclusion bodies might be consistent with a fulminant CaHV-1 infection based on a high infection level of viral genomic DNA [11].…”
Section: Introductionmentioning
confidence: 99%
“…Measuring temperature non-invasively, such as with infrared cameras, can improve welfare by reducing stress from restraining animals (Soerensen and Pedersen, 2015). Benefits of infrared are the large contrast in infrared intensity between pigs and the background environment can aid detection of pigs, especially at night (Costa et al., 2014).…”
Section: Sensors For Measuring Pig Behaviourmentioning
confidence: 99%
“…In these profiles, the mass-to-charge ratio reflects the length and composition of the acyl chain [44]. Reference ranges of acylcarnitines have been established for obese rats, adult canines, plants, and recently in horses [4548]. Lipid metabolism pathways have been extensively studied as fats are sources for flight muscle energy in some mosquito species.…”
Section: Introductionmentioning
confidence: 99%